Activation of the cAMP/protein kinase A signalling pathway by coronin 1 is regulated by cyclin-dependent kinase 5 activity - Liu X.; Bosedasgupta S.; Jayachandran R.; Studer V.; Rühl S.; Stiess M.; Pieters J. (My University, 2025)
Coronins constitute a family of conserved proteins expressed in all eukaryotes that have been implicated in the regulation of a wide variety of cellular activities. Recent work showed an essential role for coronin 1 in the modulation of the cAMP/PKA pathway in neurons through the interaction of coronin 1 with the G protein subtype Gαs in a stimulus-dependent manner, but the molecular mechanism regulating coronin 1-Gαs interaction remains unclear. We here show that phosphorylation of coronin 1 on Thr418/424 by cyclin-dependent kinase (CDK) 5 activity was responsible for coronin 1-Gαs association and the modulation of cAMP production. Together these results show an essential role for CDK5 activity in promoting the coronin 1-dependent cAMP/PKA pathway. © 2015 Federation of European Biochemical Societies.